2016
DOI: 10.18488/journal.74/2016.3.2/74.2.14.20
|View full text |Cite
|
Sign up to set email alerts
|

Managing Public Perception towards Local Government Administration

Abstract: This paper highlights the efforts by the Seremban Municipal Council in encouraging participation among local community at their administrative area. Public participation is the most vital component in a good governance model for local governments in achieving effective and efficient administration. It is very important for the local government to ensure the local community participates in the activities carried out by the council. Through interviews with public administrators of local authorities and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Residents' perception of the activities of MMDAs is crucial to the efficient delivery of local services. This is because erroneous perceptions about local government activities are likely to crowd out local participation by residents (Zulkifli et al 2016). Therefore, we include the perceived competence of MMDAs in our Tobit model and expect a positive relationship with efficiency.…”
Section: The Tobit Regression Modelmentioning
confidence: 99%
“…Residents' perception of the activities of MMDAs is crucial to the efficient delivery of local services. This is because erroneous perceptions about local government activities are likely to crowd out local participation by residents (Zulkifli et al 2016). Therefore, we include the perceived competence of MMDAs in our Tobit model and expect a positive relationship with efficiency.…”
Section: The Tobit Regression Modelmentioning
confidence: 99%
“…Residents' perception of the activities of MMDAs is crucial to the efficient delivery of local services. This is because erroneous perceptions about local government activities are likely to crowd out local participation by residents (Zulkifli et al, 2016). Therefore, we expect a positive relationship with efficiency.…”
Section: Methodology and Datamentioning
confidence: 99%
“…These studies' results might have come from research authorities but their limitations should be acknowledged. There have been concerns found from earlier literature regarding the processes of such studies, including the limited focus of analysis of these perceptions from the participants (van der Weerd et al 2011), selection criteria of participants gathered (Zulkifli et al 2017), and the development of the instrument used in gathering perceptions (Baticulon et al 2020). Studies regarding perceptions have revealed the important connection between analyzing citizens' insights and service development.…”
Section: Introductionmentioning
confidence: 99%